Meeting Point, Informal Meeting, Meeting, Meeting Room, One Day Business Trip, Interior Design. - Andereas Pandu Setiawan, Imelda Yulita Soenjoyo (Intra, 2013)
Meetings are often conducted informally in places that are not a meeting room. Besides, high activity businessmen often do one-day business trip. This activity safe more time and cost. Unfortunately, a long trip makes fatigue and tired, which is causing lack of focus at the meetings. The author sees the necessity for a meeting facility that which has a conducive atmosphere without override the function. This Meeting Point design takes place at Juanda Airport road.The concept of this Meeting Point is Informal Stimulable with Contemporary. Contemporary style is suitable to the temporary trend. Informal theme used to answer the meeting needs, that is providing lower stress levels and creating innovative thinking. Besides, the usage of stimulable theme is to ensure that the functions of a meeting room not to be forgotten. By this Meeting Point design, businessman will gain a new and functional meeting facilities